Porous Bilayer Electrode‐Guided Gas Diffusion for Enhanced CO2 Electrochemical Reduction. Issue 11 (7th June 2021) - Wang, Yucheng; Lei, Hanhui; Xiang, Hang; Fu, Yongqing; Xu, Chenxi; Jiang, Yinzhu; Xu, Ben Bin; Yu, Eileen Hao; Gao, Chao; Liu, Terence Xiaoteng
Abstract : Comparing with the massive efforts in developing innovative catalyst materials system and technologies, structural design of cells has attracted less attention on the road toward high‐performance electrochemical CO2 reduction reaction (eCO2 RR). Herein, a hybrid gas diffusion electrode‐based reaction cell is proposed using highly porous carbon paper (CP) and graphene aerogels (GAs), which is expected to offer directional diffusion of gas molecules onto the catalyst bed, to sustain a high performance in CO2 conversion. The above‐mentioned hypothesis is supported by the experimental and simulation results, which show that the CP + GA combined configuration increases the Faraday efficiency (FE) from ≈60% to over 94% toward carbon monoxide (CO) and formate production compared with a CP only cell with Cu2 O as the catalyst. It also suppresses the undesirable side reaction–hydrogen evolution over 65 times than the conventional H‐type cell (H‐cell). By combining with advanced catalysts with high selectivity, a 100% FE of the cell with a high current density can be realized. The described strategy sheds an extra light on future development of eCO2 RR with a structural design of cell‐enabled high CO2 conversion. Abstract : An advanced structured graphene aerogel–carbon paper hybrid gas diffusion electrode reaction cell offers directional diffusion of gas molecules onto the catalyst bed. The described porous bilayer configuration enables unique CO2 mass transfer features with the enhanced Faradaic efficiency of carbonaceous products over 94%, suppressing the hydrogen evolution reaction and considerable durability as a result of electrolyte permeation prevention.